Answer:
Below
Step-by-step explanation:
Substituting the given values:
f(6) = 6(2/3) - 2 = cube root of 6^2 - 2 = cube root 36 - 2
f(-6)= (-6)(2/3) - 2 = cube root of(-6)^2 - 2 = cube root 36 - 2
So This is true,
f(6) = cube root of 6^2 - 2 = cube root 36 - 2 = 1.3019
2 * f(3) = 2 * (cube root of 3^2 - 2 ) = 2 * (cube root of 9 - 2) = 0.1602
So False,
Tom bought 768 pounds of candy because 333 + 435 = 768
Answer:
Step-by-step explanation:
I'm unsure why my answer was deleted, randomly deleted a thoroughly explained answer.
20% is 20/100, 1/5, or 0.2
The number will decrease by a factor of 5.
Answer:
y = -49
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Step-by-step explanation:
<u>Step 1: Define</u>
-7 = y/7
<u>Step 2: Solve for </u><em><u>y</u></em>
- Multiply 7 on both sides: -49 = y
- Rewrite: y = -49